(untitled) (Международный научный журнал «Инженер», 2026)
In the conditions of digitalization of the transport sector, the development of innovative train traffic control systems becomes very important. Such systems must provide high reliability, safety, and efficiency of the transportation process. Traditional signaling methods, based on track circuits and electromechanical relays, have several limits: they are sensitive to electromagnetic noise, use more energy, have delays in fault diagnostics, and need high maintenance costs. This paper presents a developed system for signal control and information exchange on railway lines. The system is based on the integration of microcontrollers, ACS712 current sensors, inductive sensors, RFID modules, and fiber-optic data channels. The structural diagram of the traffic light control unit is analyzed, the functions of the main elements are described, and a digital comparison of the parameters of traditional and modern systems is made. The results show that the proposed solution increases the reliability of data transmission by 10 times, reduces signal delay 20–30 times, decreases energy consumption up to 60%, and lowers maintenance costs by 30–40%.